Synthesis and Characterization of Metal Complexes of Copper(II), Nickel(II) ans Cobalt(II) with Bis-(1,2-Diphenyl-1-Hydroxyimino-2-Ethylidene) 1,3-Diamino Benzene - Sahu, K.; Chandra Yadav, Shiv; Mahto, Kailasha (Asian Journal of Chemistry, 2010)
The ligand bis-( 1,2-diphenyl-1-hydroxyimino-2-ethylidene)-1,3- diamino benzene reacts with metal acetates to give inner complex of the type M2L2, where M = Cu(II) and M2L2.4H2O where M = Ni(II) and Co(II). The neutral complexes of Cu(II) are devoid of water molecules while Ni(II) and Co(II) complexes are found to contain four molecules of water. Besides the neutral complexes, complexes of other two different series such as M2(LH2)X4 where M = Cu(II) and X = Cl-, Br-, I-, NO3- and M2(LH2)X4, where M = Co(II) and Ni(ll); X = Cl-, Br-, I-, NO3-, have been prepared where the ligand co-ordinates with the metal ion in its uncharged form. IR electromc spectra and magnetic moment measurements have been used to characterize the compounds.